Th/U ratios in metamorphic zircon - Yakymchuk, C.; Kirkland, Chris; Clark, Christopher (Wiley - Blackwell, 2018)
The Th/U ratios of zircon crystals are routinely used to help understand their growth mechanism. Despite the wide application of Th/U ratios in understanding the geological significance of zircon U-Pb ages, the main controls on the Th/U ratio in metamorphic zircon are poorly understood. Here, phase equilibria modelling coupled with solubility expressions for accessory minerals are used to investigate the controls on the Th/U ratios of suprasolidus metamorphic zircon in an average amphibolite facies metapelite composition. We also present a new database of metamorphic Th/U ratios in zircon from Western Australia. Several factors affecting the Th/U ratio are investigated, including the bulk rock concentrations of Th and U, the amount of monazite in the system, and open v. closed system behaviour. Our modelling predicts that the main controls on the Th/U ratio of suprasolidus metamorphic zircon are the concentrations of Th and U in the system, and the breakdown and growth of monazite in equilibrium with zircon. Furthermore, the relative timing of zircon and monazite growth during cooling and melt crystallization has an important role in the Th/U ratio of zircon. Early grown zircon near the peak of metamorphism is expected to have elevated Th/U ratios whereas zircon that grew near the solidus is predicted to have relatively low Th/U ratios, which reflects the coeval growth of monazite during cooling and melt crystallization. Our modelling approach aims to provide an improved understanding of the main controls of Th/U in metamorphic zircon in migmatites and hence better apply this geochemical ratio as a tool to assist in interpretation of the genesis of metamorphic zircon.